Sustainable Development Goals Analysis at Setu Village in Tegal Using COBIT 4.1 - Isnaeni Rachmawati; Resad Setyadi (Soegijapranata Catholic University, 2023)
The role of Modern Technology (IT) is growing and is needed by many agencies including the government, one of which is Information Technology Governance (ITG). ITG has a role in relevant agencies related to IT and the best services to help staff and community activities become important related to the village head office business. The purpose of this study is to analyze IS risk management at the Setu Village Head Office using the Framework Control Objective for Information and Related Technology (COBIT) 4.1. This study uses quantitative research methods by distributing questionnaires to respondents. The questionnaire got the data validity and reliability test well. The data will be analyzed and get the results showing the maturity level at level 3 meaning that the values are in the specified position. To achieve the goal through a much more structured way, namely using assets from the organization that are owned and well defined. Recommendations for this research are the need for additional infrastructure such as computers, wifi or others and the addition of human resources in the IT department at the Setu Village Head Office